AKUNTANSI UNTUK INSTRUMEN KEUANGAN - , FRANSISKA VENA A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
On January 1, 2010 banking industry in Indonesia has been applying SFAS No.50 and SFAS No.55 revised 2006 adopted from IAS 32 and IAS 39. SFAS No.50 and SFAS No.55 revised 2006 are the most complicated standard. The standards also potentially create earnings volatility. The application of SFAS No.50 and SFAS No.55 revised 2006 has strategic purpose specifically for inviting investors from stock market and money market. However, there is no research explaining about the impact of applying SFAS No.50 and SFAS No.55 revised 2006 toward investorâs reactions in Indonesia. The paper aims to examine the impact of banking industry in Indonesia after applying SFAS No.50 and SFAS No.55 revised 2006. Specifically, this paper aim to provide empirical evidences on the impacts of applying SFAS No.50 and SFAS No.55 revised 2006 toward investorâs reactions in Indonesia. The sample used in this research is 30 companies listed in Indonesian Stock Exchange (IDX) from period January 1, 2010 until December 30, 2010. Researcher used event study approach with -5+2 days research windows around the IDX announcement date . It can be concluded from the t-test that companyâs profitability was significantly different after applying SFAS No.50-55 revised 2006. And from regression analysis we can concluded that companiesâ performance also has an impact on stock return in the announcement date and one day after it. And then it can be concluded also from the regression result that the implementation of SFAS No.50 and SFAS No.55 revised 2006 statistically insignificant associated with investor reaction. And there is no negative effect attributable to the implementation of SFAS No.50 and SFAS No.55 revised 2006. The result shows that investors do not consider the volatility from implementation SFAS No.50 and SFAS No.55 revised 2006 in their decision making. The sample firms also reported an absolute cumulative effect on income Rp388.276.908.115 which is positive